Verso e reverso das medidas protetivas de urgência: atuação da Vara Especial de Violência Doméstica e Familiar contra Mulher na Comarca de São Luís/MA, à luz da Lei Maria da Penha - REIS, Luanne Silva (2019)
The present study deals with domestic and family violence against women and aims to analyze the performance of the Special Stick of Domestic and Family Violence against Women of São Luís County / MA-Women Stick in the application of urgent protective measures - MPU, in the light of Law 11340/06-Maria da Penha Law, from a gender perspective. It starts from the understanding of domestic and family violence as a participant in a broader violence, gender violence, which involves complex relationships that combine domination, hierarchy, power and gender inequality, in which masculine supremacy occurs. These relations are structural and structuring of society and are legitimized, even by the institutions that, a priori, guarantee the rights of women. In order to meet the desired objectives, a quantitative and qualitative approach is used, through documentary research, in which data collection and analysis occurs in 66 processes of urgent protective measures-MPU filed in 2016 by Vara da Mulher from São Luís / MA. From the information obtained, it is possible to characterize domestic and family violence for a better contextualization of the phenomenon and, subsequently, the analysis of the procedural rites used by the institution in the application of urgent protective measures to face domestic and family violence against them. women, correlated the material collected with the categories that guide the research. From the results obtained in this research, it appears that the slowness and omission of the judiciary returns domestic violence and family to the private sphere of relations and, once again, abstains the state from its confrontation.